Organisational Culture Transformation at Bengkulu Company: 2024 Trends in Improving Employee Engagement - Saputri, Vettyca Diana; Susena, Karona Cahya; Tarigan, Heskyel Pranata (Innovative Business Management Journal, 2024)
This research highlights the importance of organisational culture transformation in companies in Bengkulu in the face of 2024 management challenges and trends. An adaptive and effective organisational culture is the foundation for an inclusive and productive work environment. This article focuses on several important trends, such as work flexibility, employee mental and physical well-being, and the application of diversity and inclusion (DEI) principles. Cultural transformation is not only a response to external changes, but also a strategy to increase employee engagement, i.e. a sense of involvement and ownership of the company. By creating a supportive work environment, companies in Bengkulu can increase employee loyalty and minimise turnover. In addition, an organisational culture that is aligned with new trends is predicted to make it easier for companies to attract the best talent amidst the increasingly fierce labour market competition.This article also proposes some concrete strategies that can be implemented by companies in Bengkulu, such as implementing hybrid working models, improving wellness programmes, and ensuring that diversity policies are consistent. These recommendations are expected to help companies transform more sustainably. With the adoption of the right strategies, this cultural transformation will be an important factor in improving employee engagement while ensuring business continuity in an era of dynamic change